Genetic analysis of carrier status in female members of Japanese hemophilia families. (5th May 2021) - Shinozawa, Keiko; Amano, Kagehiro; Hagiwara, Takeshi; Bingo, Masato; Chikasawa, Yushi; Inaba, Hiroshi; Kinai, Ei; Fukutake, Katsuyuki
Abstract: Background: Genetic characteristics and genetic carrier diagnosis in Japanese hemophilia female carriers have not been evaluated. Objectives: To provide genetic information on Japanese hemophilia female carriers and demonstrate the advantages of genetic testing in carrier diagnosis. Methods: DNA sequencing combined with long polymerase chain reaction for inversion and multiplex ligation‐dependent probe amplification for large mutations. Results: Genetic analysis was performed in 69 male hemophiliac patients (48 hemophilia A [HA] and 21 hemophilia B [HB]) and 112 female family members (FFM) (80 from 50 families with HA and 32 from 22 families with HB). In 72 hemophiliac families, the identified F8 mutations were inversion (42%), missense (26%), and other variations (32%), while 74% of F9 mutations were point mutations. Among the 112 FFM, 53/80 (66%) with HA and 21/32 (66%) with HB were diagnosed genetically as carriers based on detection of heterozygous mutations. Low factor VIII activity (FVIII:C) levels (<50 IU/dL) were detected in only 10% of gene‐confirmed carriers, suggesting that FVIII:C is not suitable for HA carrier prediction. Low FVIII/von Willebrand factor ratio (<0.9) was observed in 67% of gene‐confirmed carriers. Half of the gene‐confirmed HB carriers had low FIX:C (<60 IU/dL). Importantly, 32 mothers of 37 sporadic cases (86%) (24/27 [89%] HA and 8/10 [80%] HB) showed the relevant mutations, suggesting low incidence of de novo mutations in males. Conclusions: This study is the first to provide genetic information on Japanese hemophilia female carriers. Gene analysis is the gold standard for carrier diagnosis as it well identifies undetected female carriers based on pedigree information and hemostatic measurements.